Lightweight thermally insulating fired clay bricks enhanced with chitosan-based clay nanocomposites for sustainable construction - M. Abdelhamid Shahat; Wafaa Soliman (Scientific Reports)
Abstract This study explores the enhancement of thermal insulation in fired clay bricks through the incorporation of chitosan (CS) as a biopolymeric dopant. A series of composite samples were prepared with CS concentrations of 0%, 2%, 4%, 6%, and 8%, and their structural, mechanical, and thermophysical qualities were comprehensively investigated. Analytical techniques including X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and thermogravimetric analysis (TGA) were employed to assess compositional and morphological changes. The introduction of CS led to increased XRD peak intensity, indicating improved crystalline organization, while FTIR spectra revealed the presence of CS-associated functional groups. SEM micrographs confirmed the development of a more porous microstructure, and TGA data demonstrated enhanced thermal stability. The CS-modified bricks exhibited an increase in porous topography (33.2–47.9%), a reduction in bulk density (i.e., 1.84–1.29 g/cm3), and improved compressive strength (from 0.768 to 1.232 MPa). It is noteworthy that the clay@CS (6%) mix encountered a low thermal diffusivity in addition to the lowest thermal conductivity value (i.e., 0.3418–0.2334 W/mk). The findings show that adding more CS to composite bricks significantly improves their thermal insulation qualities (i.e., 0.314–0.213 mm2/S). These outcomes underscore the potential of CS as a sustainable additive for improving the performance of clay-based construction materials, offering promising implications for energy-efficient and environmentally conscious building applications.